SOSIALISASI MENANAM HARAPAN UNTUK MASA DEPAN LESTARISEBAGAI UPAYA PENCEGAHAN POLUSI UDARA KABUPATEN BOJONEGORO - Solikhati Indah Purwaningrum; Nindy Callista Elvania; Winda Uswatun Khasanah; Jannatul Firdausi Ahla (Jurnal Abdi Masyarakat, 2025)
Air pollution is the entry of polluting substances into the air consisting of gases and small particles or aerosols.  Conditions of increasing air pollution (air pollution) affect public health and environmental quality. Air pollution includes particles (dust, aerosols, lead, and CO), as well as gases (NOx, NOx, SOx, H2S, and hydrocarbons). There are many negative impacts that can be caused by air pollution, it is necessary to increase awareness of the various dangers that can occur in In the future, the need for a social approach is an effort to increase awareness of the environment. A social approach takes the form of outreach with didactic teaching methods regarding air pollution and efforts to reduce air pollution. socialization What was done was successful in increasing students' knowledge regarding efforts to prevent air pollution. There is a need for further assistance to students to increase understanding and cultivate a sense of care and love for the environment so that SMA Negeri 1 Malo can be used as a role model for environmental conservation.